A novel connection between the Cell Wall Integrity and the PKA pathways regulates cell wall stress response in yeast - Raúl García (Nature Portfolio, 2017)
Abstract Fungal cells trigger adaptive mechanisms to survive in situations that compromise cell wall integrity. We show here that the global transcriptional response elicited by inhibition of the synthesis of β-1,3-glucan by caspofungin, encompasses a set of genes that are dependent on Slt2, the MAPK of the Cell Wall Integrity (CWI) pathway, and a broad group of genes regulated independently of Slt2. Genes negatively regulated by the cyclic AMP/Protein Kinase A (PKA) signaling pathway were overrepresented in the latter group. Moreover, cell wall stress mediated by inhibition of β-1,3-glucan synthesis, but not by other cell wall interfering compounds, negatively regulated PKA signaling as indicated by the nuclear localisation of Msn2, cellular glycogen accumulation, a decrease of intracellular cAMP levels and a severe decrease in both the activation of the small GTPase Ras2 and the phosphorylation of known substrates of PKA. All these effects relied on the plasma membrane-spanning sensor of the CWI pathway Wsc1. In addition, caspofungin induced a reduction in the cytosolic pH, which was dependent on the extracellular region of Wsc1. Therefore, alterations of the β-1,3-glucan network in the fungal cell wall, induce, through Wsc1, the activation of the CWI pathway and parallel inhibition of PKA signaling.